Lia Suri online system - Siti Nur Aisyah, Mohd Sani (2019)
Online shopping is an application which allow customer to purchasing directly Lia Suri enterprise’s products over the internet by using a web browser. In this era, time is the most crucial thing in life. In my observation, I found that some people in this world did not have time to purchase their needs. As the result, majority of customer choose to make purchase by online. Lia Suri Online System is an online management which will change from manual or electronic fund to online payment. The purpose of this study are to provide alternative way for the customer to purchase Lia Suri’s product which is by online shopping, to study Lia Suri online system from manual to computerize and then evaluate the proposed prototype system in web based. This system also let Lia Suri‘s enterprise as an administrator of the system to monitor and update on the product and also generating the report. The appropriated of method was applied to develop this system. The methodology that have been proposed for this system is Rapid Application Development (RAD) because this methodology can develop the system faster and produces higher quality at the same time. RAD consists of four phases, which are Requirements Planning, User Design, Construction, and Cutover. After development is done, User Acceptance Test (UAT) is being process, where actual customers test the software to make sure it can handle required tasks in real-world scenarios according to its specifications stated.